Comparison of self-reported & device-based, measured physical activity among children in Germany - Alexander Burchartz; Doris Oriwol; Simon Kolb; Steffen C. E. Schmidt; Kathrin Wunsch; Kristin Manz; Claudia Niessner; Alexander Woll (BMC, 2021)
Abstract Background As children show a more complex but less structured movement behavior than adults, assessment of their many spontaneous and impulsive movements is a challenge for physical activity (PA) assessment. Since neither questionnaires nor accelerometers enable optimal detection of all facets of PA, a multimodal, combined approach of self-reported and device-based methods is recommended. Based on the number of days on which the participants reached the physical activity (PA) values given in the WHO guideline, this study examines 1) the difference between self-reported and device-based, measured PA and 2) whether PA differences between age and gender groups obtained by two methods are comparable. Methods Participants aged 6-17 years were randomly chosen and data were collected representatively at 167 sample points throughout Germany within the Motorik-Modul Study. PA of n = 2694 participants (52.3% female) was measured using the ActiGraph accelerometer (ACC) and a physical activity questionnaire (PAQ). The sample was divided into three age groups (6-10 yrs. n = 788, 11-13 yrs. n = 823, 14-17 yrs. n = 1083). Numbers of days per week with at least 60 min moderate to vigorous PA (MVPA) were analyzed for both methods. Results Only every 25th respondent (4%) reaches the WHO standard of 60 min MVPA every day if measured with ACC. Self-reported PA was slightly higher (9%) (meanPAQ = 3.82 days; meanACC = 2.34 days; F method  = 915.85; p = <.001; f Cohen  = .64). The differences between the methods are significantly smaller in younger children than in the older age groups (F age  = 264.2, p < .001; f Cohen  = .48). The older the subjects are, the lower is the proportion of those who meet the WHO guideline on each day, with girls meeting the guideline less frequently than boys in all age groups. Conclusion Children and adolescents living in Germany show a very low adherence to the WHO guideline on PA. While younger children are much more active with their free play, especially children over 10 years of age and especially girls should be the target of programs to increase PA.